Effect of head impacts on diffusivity measures in a cohort of collegiate contact sport athletes - McAllister, Thomas W. (Lippincott Williams & Wilkins, 2014)
OBJECTIVE: To determine whether exposure to repetitive head impacts over a single season affects white matter diffusion measures in collegiate contact sport athletes. METHODS: A prospective cohort study at a Division I NCAA athletic program of 80 nonconcussed varsity football and ice hockey players who wore instrumented helmets that recorded the acceleration-time history of the head following impact, and 79 non–contact sport athletes. Assessment occurred preseason and shortly after the season with diffusion tensor imaging and neurocognitive measures. RESULTS: There was a significant (p = 0.011) athlete-group difference for mean diffusivity (MD) in the corpus callosum. Postseason fractional anisotropy (FA) differed (p = 0.001) in the amygdala (0.238 vs 0.233). Measures of head impact exposure correlated with white matter diffusivity measures in several brain regions, including the corpus callosum, amygdala, cerebellar white matter, hippocampus, and thalamus. The magnitude of change in corpus callosum MD postseason was associated with poorer performance on a measure of verbal learning and memory. CONCLUSION: This study suggests a relationship between head impact exposure, white matter diffusion measures, and cognition over the course of a single season, even in the absence of diagnosed concussion, in a cohort of college athletes. Further work is needed to assess whether such effects are short term or persistent.